2013
DOI: 10.5604/12314005.1136157
|View full text |Cite
|
Sign up to set email alerts
|

Self-Reported Drivers’ Behaviour: An Application of DBQ in Poland

Abstract: Most of road accidents are caused by human error. To study these errors road safety researchers developed selfreported measures. DBQ (Driver Behaviour Questionnaire) is one of the most frequently used tools for studies carried out in scope of traffic psychology. It has become an international standard which is used by driver behaviour researchers, yet it is still quite unknown in Poland. The questionnaire describes aberrant behaviour of the drivers in two basic dimensions: errors and violations. The main purpo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
14
0

Year Published

2017
2017
2020
2020

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 13 publications
(15 citation statements)
references
References 14 publications
1
14
0
Order By: Relevance
“…Drivers' with lack of sufficient driving experience caused to increase the chance of the occurrence of fatal accidents as compared to those with long years of driving experiences. This may be because lower driving experience drivers usually involve in driving faster than the recommended limits [50][51][52][53]. Another similar study reveals that less experienced drivers were the most significant cause of fatalities than the experienced drivers, as inexperienced drivers may not predict very well what will happen on the roadways [54].…”
Section: Discussionmentioning
confidence: 99%
“…Drivers' with lack of sufficient driving experience caused to increase the chance of the occurrence of fatal accidents as compared to those with long years of driving experiences. This may be because lower driving experience drivers usually involve in driving faster than the recommended limits [50][51][52][53]. Another similar study reveals that less experienced drivers were the most significant cause of fatalities than the experienced drivers, as inexperienced drivers may not predict very well what will happen on the roadways [54].…”
Section: Discussionmentioning
confidence: 99%
“…Driving style of the participants was assessed on the basis of the Driver Behavior Questionnaire (DBQ) before the main experiment. The survey uses questions from a study by Reason and others [102] with further modifications [103,104]. For the purpose of this research, two factors measured by the DBQ were taken into account: conscious violations and tactical mistakes of drivers.…”
Section: Methodsmentioning
confidence: 99%
“…This result was similar to previous studies in Addis Ababa [13,19]and Bahir Dar city [12].The driving experience of less than 5 years wasassociatedwith a higher human death perroad traffic accidents as compared to those who have more than 5 yearsdriving experience. Similarly, prior studies reported that the smaller driving experience the higher probability of experiencing human deaths per accident [16][17][18]. Among vehicle types, numbers of deaths due to road traffic accidents by automobiles weresignificantly greater than other vehicle types.…”
Section: Discussionmentioning
confidence: 56%
“…The response variable of this study was the number of human deaths per road traffic accident in Oromia region measured as 0, 1, 2, 3…A human death includes pedestrians, road users, passengers or other peoples dead due to road traffic accident. The potential predictors related to the number of human deaths per road traffic accident adopted from various literature [16][17][18][19][20][21][22]…”
Section: Variables Of the Studymentioning
confidence: 99%